The Effect of NPF and FDR on The Profitability of Sharia Commercial Banks with Murabahah Financing as Moderation - Hasan Abdul Azis Naibaho, Muhammad; Maulidizen, Ahmad (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to examine the influence of Non-Performing Financing (NPF) and the Financing to Deposit Ratio (FDR) on Return on Assets (ROA), while also assessing the moderating role of Murabahah financing in these relationships within Islamic Commercial Banks in Indonesia during 2018–2022. Method – The research uses a quantitative method supported by library research, involving moderated regression analysis with classical assumption tests, model feasibility tests, and hypothesis testing. The sample includes 10 Islamic banks selected through purposive sampling from a population of 17 registered with the Financial Services Authority. Findings – The findings reveal that NPF does not significantly affect ROA, while FDR negatively affects ROA. Murabahah financing moderates both the NPF–ROA and FDR–ROA relationships. Theoretically, this research contributes to Islamic banking performance literature, especially regarding the role of specific financing instruments. Implications – Practically, it implies that Islamic banks should diversify their financing portfolios, expand funding sources, and strengthen risk management to enhance profitability. Murabahah financing can help reduce credit risk, though it may elevate liquidity risk, requiring careful portfolio and liquidity planning